A new validated HPLC method for the determination of quercetin: Application to study pharmacokinetics in rats. (21st September 2016) - Abdelkawy, Khaled S.; Balyshev, Mark E.; Elbarbry, Fawzy
Abstract: A simple, accurate, and reproducible high‐performance liquid chromatography (HPLC) method has been developed and validated for the quantification of quercetin (QR) in rat plasma. The method involves a simple protein precipitation procedure to extract both QR and thymoquinone (TQ), the internal standard. The chromatographic analysis was achieved on a Shimadzu LC 20 A HPLC system equipped with a Supelcosil LC‐18 T C18 column and an isocratic mobile phase consisting of 0.3% trichloroacetic acid in water and acetonitrile HPLC‐grade (50:50, v /v) run at a flow rate of 0.9 mL/min for 13 min. The UV detection wavelength was set at 254 nm. The method exhibited good linearity ( R 2 > 0.994) over the assayed concentration range (0.10–25 μg/mL) and demonstrated good intra‐day and inter‐day precision and accuracy (relative standard deviations and the deviation from predicted values were <20%). This method was also successfully applied for studying the pharmacokinetics of QR in rats following a single oral dose of QR to evaluate its pharmacokinetic parameters in rats.